KNOWLEDGE AND UNDERSTANDING OF ACT PROMULGATING THE NARCOTICS CODE 2021 AMONG OFFICERS AT THE OFFICE OF THE NARCOTICS CONTROL BOARD BANGKOK - หยกอุบล สุทธินัย; โกวงศ์ ศรีรัฐ (Thai Interdisciplinary and Sustainability Review, 2024)
The objectives of this research were to study the level of knowledge and understanding of Act Promulgating the Narcotics Code 2021 among officers of the Office of the Narcotics Control Board and compare such knowledge and understanding by demographic factors. The sample was 74 officers from the Office of the Narcotics Control Board Bangkok. The result of this study found that the level of knowledge and understanding of Act Promulgating the Narcotics Code 2021 among officers of the Office of the Narcotics Control Board was high overall. The hypothesis testing found that the differences in age, educational degree, work position and duration of work differently affected the level of knowledge and understanding of the Narcotics Code among officers of the Office of the Narcotics Control Board. Therefore, a recommendation to the Office of the Narcotics Control Board should establish and produce media. Organizing regular training on knowledge and understanding of the Narcotics Code for officer in the office. The office of the Narcotics Control Board can use the results of this study. to be produced as academic media according to the matter that officers still have insufficient knowledge and understanding.